Influence of Temperament on the Acceptance of Two Conscious Sedation Techniques in Toddlers Undergoing Dental Treatment: A Randomised Cross Over Trial - Palak Janiani; Deepa Gurunathan; Sivakumar Nuvvula (Pain Research and Management)
Background. Pediatric dentists often find it challenging to handle pediatric patients due to their fear, unease, and anxiety toward dental procedures. To address this, sedation agents such as intranasal midazolam and nitrous oxide are commonly used as pharmacological behavior management methods. A child’s temperament affects their behavior in unfamiliar settings. Aim. To study the effect of child temperament on the acceptance of the nasal mask and intranasal drug administration in children undergoing dental treatment. Methods. Thirty-two anxious children aged three to five were randomly assigned to two groups. During the first visit, one group received intranasal midazolam sedation, while the other group received nitrous oxide administered through a mask. On the subsequent visit, the groups crossed over. The parent assessed the child’s temperament, and the acceptance of the sedation methods was recorded. The Ohio State University Behavioral Rating Scale (OSUBRS) was employed to assess behavior during the administration of local anesthesia. Statistical analysis was carried out using the chi-square test and Mann–Whitney U test (p value <0.05). Results. Children exhibited greater acceptance of the nasal mask compared to using the intranasal route for delivering midazolam during the induction process. A significant statistical influence of temperament was observed on the acceptance of the nasal mask and the intranasal atomisation device (p value <0.05). The mean OSUBRS scores did not show any statistically significant differences between the sedation groups (p = 0.14). Conclusion. Most children demonstrated a more favorable acceptance of the nasal mask during the induction process; however, intranasal midazolam can serve as an effective alternative for anxious patients who struggle to keep the nitrous oxide mask on during the dental procedure. The adoption of these methods is influenced directly by the child’s temperament.